Šulgi and Gilgameš: Two Brother-Peers (Šulgi О) - Klein, Jacob
edition of Šulgi O; SLTN 79, UM 29-15-9 + 29-15-158, CBS 10306, Ni 4112 (ISET 1 pl. 72), Ni 4101 (ISET 1 pl. 27), CBS 10900, Ni 13227 (ISET 1 pl. 150).